(untitled) (TSUL LEGAL REPORT, 2026)
The study provides, giving a detailed legal definition of the criminal structure of crimes of torture and other cruel, inhuman or degrading treatment or punishment, comparative and legal analysis of national and foreign legislation on liability for torture and related crimes with the usage of international conventions, qualification of torture and other cruel, inhuman or degrading treatment. In addition, clear and detailed proposals have been put forward to improve the legislation, in particular the Criminal Code, through the study of international experience and norms of international law. A number of recommendations have been developed for a fundamental improvement in law enforcement practice, with an analytical and legal analysis of existing shortcomings in the legal system based on the results of data on cases of torture. With this topic it is clarified the composition of crimes related to torture and other illegal treatment or punishment. The subjective and objective sides of the crime and the basis of qualification, as well as its problems on qualifying the crime are clearly defined.